PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN MANUFAKTUR: STUDI EMPIRIS TATA KELOLA - DYLAN BILLY JAPOETRA; YULIUS KURNIA SUSANTO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
This study is aim to examine the effect of managerial ownership, public ownership, board independence, audit committee, and board size on corporate sosial responsibility disclosure. This research is developed based on the previous research by Khan et al. (2013). The sample uses in this research is based on the data 180 manufacturing companies listed in Indonesia Stock Exchange during years 2014-2016. Sample are selected using purposive sampling method. Data analysis was using multiple regression analysis.The result showed that the public ownership, and board size have positive influence on corporate sosial responsibility disclosure. While managerial ownership, board independence, audit committee have no effect on the disclosure of corporate social responsibility.